KAJIAN INTERAKSI KERUANGAN SERTA SEKTOR POTENSIAL WILAYAH KECAMATAN SYIAH UTAMA KABUPATEN BENER MERIAH - Devna Devna; Cut Zukhrina Oktaviani; Noer Fadhly (Prodi Magister Teknik Sipil Unsyiah, 2022)
Planning a new urban area as an alternative to a new growth center in an area requires a special strategy in understanding the characteristics and potential of the area. Geographically, Samar Village Refinery Main Shiite District Bener Meriah regency has the opportunity to become a new urban area because it is directly adjacent to North Aceh and East Aceh regencies. The purpose of this study is to examine spatial interaction and the selection of business sectors that will be developed in the Syiah Utama Subdistrict area. The methods used in this research are quantitative methods using Gravity Model theory analysis, Stop Point Theory analysis, and Static Location Quotient (SLQ) analysis. The results of the analysis showed that the potential for faster growth of Syiah Utama Subdistrict towards North Aceh Regency with spatial interaction of 10,496,116 and a functional area limit of 4,199.35 hectares, while the selection of suitable business field sectors developed as base / potential sectors are the agriculture sector, forestry sector, fisheries sector, construction sector, financial services sector, and insurance.